Starość w żywotach mnichów palestyńskich Cyryla ze Scytopolis - Twardowska, Kamilla (Vox Patrum, 2011)
The problem of went by time is very often in The Lives of the Monks of Palestine written about by Cyril of Scythopolis, famous monk and writer, who lived during first part of VIth century. His main heroes lived very long e.g. Cyriacos died when he was 107, Eutymios – 97, Saba – 94, John Hesychast – 104, Teodosius – 99, – such age was a sign of God’s mercy. Cyril used to write about old monk who was a teacher to young ones, and he created a topos: old means wise, experience; youth – impatience, and to be open for everything which come from laic world. Cyril wrote we shouldn’t be afraid of old age, on the contrary we should wait for this. Old men did wonderful things by founding monasteries, working miracles, playing active in religion and politics. They were paragon of virtue to everyone. What monks at the Judean Desert did to live so long. The first thing was God’s mercy, but the secondo one – very special diet – almost vegetarian.